Promoting Tolerant Religious Understanding: The Effectiveness of Pengajian Al-Hidayah among Mothers in the Air Putih District - Luthfiah, Hany Tasya; Soiman, Soiman (Jurnal Dakwah dan Komunikasi, 2024)
The lack of interest among mothers in understanding and accepting views or beliefs that differ from those held by other individuals or groups in a religious context exacerbates cases of intolerance. Consequently, there are still mothers who reject the presence of new Muslim neighbors in their community and avoid interacting with them due to religious differences. This study aims to explore the effectiveness of Al-Hidayah study sessions in enhancing the religious understanding of mothers in the Air Putih District. Through qualitative research and direct experience, this study investigates positive changes in the level of religious understanding and behavior of mothers after participating in the study sessions. The results indicate that Al-Hidayah study sessions have an impact on delving into tolerant Islamic values, evidenced by the increase in religious understanding regarding fiqh ibadah, akhlak, and aqidah based on tolerance. Al-Hidayah study sessions provide insight into how tolerance becomes an important instrument in shaping the spirituality and well-being of mothers in the Air Putih District. Al-Hidayah study sessions play a central role in creating a spiritually stronger community, and by involving mothers in discussions, factors influencing these study sessions can also be observed. This research focuses on the local context, specifically in the Air Putih District.